Demographic Characteristics and Noneconomic Outcomes of Women Entrepreneurs with Moderation of Barriers: The Case of Small Enterprises in Rural Coastal Area of Indonesia - Ika Nur Putriantini; Yoshi Takahashi (Jurnal Perikanan Universitas Gadjah Mada, 2020)
As a means of escaping poverty, women often become entrepreneurs while maintaining a traditional occupation and this may limit their ability to take full advantage of entrepreneurial opportunities. This study provides a relevant examination of women entrepreneurs in a rural coastal area of a developing country; as such, it helps contribute to perspectives on demographic characteristics, on the barriers to, and the noneconomic outcomes of women entrepreneurs in the rural areas of developing countries. The results demonstrate that all the demographic characteristics of women entrepreneurs correlate significantly with noneconomic outcomes. Meanwhile, only three of five barriers were found to moderate the relationship between the demographic characteristics and noneconomic outcomes. These barriers are likely to affect the real-world relationship between the demographic characteristics and non-economic outcomes. For that reason, great attentions need to be given for policy makers to improve the presence of small enterprises.